Clinical and molecular analysis of JCPyV and BKPyV infection and associated risk of urothelial carcinoma development in the upper tract - Chun-Nun Chao; Chi-Feng Hung; Wei‑Hong Lai; Chun-Liang Tung; Wan-Yun Yeh; Kai-Wu Yang; Meilin Wang; Ya-Yan Lai; Pei-Lain Chen; Cheng-Huang Shen (Virology Journal)
Abstract Background Human polyomaviruses (HPyVs), JC polyomavirus (JCPyV) and BK polyomavirus (BKPyV), have been found in upper tract urothelial carcinoma UTUC; however, the association of the viral oncogenic factors and clinical characteristics of UTUC remains unclear. This study aimed to investigate the prevalence of JCPyV and BKPyV in UTUC and their correlation with cancer progression among the southwest Taiwanese population from 2020 to 2022. Methods A total of 72 paraffin-embedded UTUC tissue samples and 41 adjacent tissue samples were collected from 72 patients. Nested polymerase chain reaction and DNA sequencing were used to detect viral DNA and genotypes. Immunohistochemistry was performed using anti- large T (LT) and anti-p53 monoclonal antibodies to detect the expression of viral early LT protein and cellular p53 protein, respectively. Results The overall prevalence of JCPyV and BKPyV were higher in UTUC than in adjacent tissue samples (65.3% [47/72] vs. 17.1% [7/41]). JCPyV and BKPyV were detected in 95.7% (45/47) and 4.3% (2/47) of the HPyVs-positive UTUC samples, respectively. JCPyV-TW-3 was the predominant strain of JCPyV infection. In UTUC samples, the LT protein of JCPyV and BKPyV positivity rate was 65.3%, while that of mutant p53 protein was 52.7%. JCPyV infection and LT protein expression increased the odds ratio (OR) of UTUC by 9.13-fold. The OR of UTUC was higher by 10.34-fold in patients with mutant p53 and by 10.37-fold in those with simultaneous LT and mutant p53 expression. The presence of LT protein in UTUC patients may increase the OR of mutant p53 protein expression by 2.93-fold compared to its absence. Women had a 5.19-fold higher superiority of JCPyV infection and LT expression than men. Patients with chronic kidney disease (CKD) had a 3.15-fold higher OR for mutant p53 protein expression than those without it. In the UTUC advanced stages, the OR of virus and LT expression was 3.18-fold higher compared to those who do not require chemotherapy. Conclusions JCPyV infection is highly prevalent in UTUC, and the presence of CKD concurrent with high expressions of LT and mutant p53 proteins in patients may be a useful indicator for chemotherapy and poor prognosis.